2011
DOI: 10.3390/ijerph8103844
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pesticides in Active and Depopulated Beehives in Uruguay

Abstract: The influence of insecticides commonly used for agricultural purposes on beehive depopulation in Uruguay was investigated. Honeycombs, bees, honey and propolis from depopulated hives were analyzed for pesticide residues, whereas from active beehives only honey and propolis were evaluated. A total of 37 samples were analyzed, representing 14,800 beehives. In depopulated beehives only imidacloprid and fipronil were detected and in active beehives endosulfan, coumaphos, cypermethrin, ethion and chlorpyrifos were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 29 publications
3
53
0
7
Order By: Relevance
“…The continuous increase of soybean monocultures in SA indirectly affects colony survival in two main ways: a) By loss of local flora available, which provides diversity in nectar and pollen source, relevant for a successful immune response ; and b) By the use of pesticides; sudden mortality of bees is usually associated with pesticide use (Malaspina et al 2008). Pesticides have been blamed for honeybee losses in many regions of Brazil, especially in agriculture zones , and also in Uruguay (Pareja et al 2011). In the latter country, fipronil and imidacloprid have been detected in high doses in depopulated colonies.…”
Section: Agricultural Intensification and Use Of Pesticidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The continuous increase of soybean monocultures in SA indirectly affects colony survival in two main ways: a) By loss of local flora available, which provides diversity in nectar and pollen source, relevant for a successful immune response ; and b) By the use of pesticides; sudden mortality of bees is usually associated with pesticide use (Malaspina et al 2008). Pesticides have been blamed for honeybee losses in many regions of Brazil, especially in agriculture zones , and also in Uruguay (Pareja et al 2011). In the latter country, fipronil and imidacloprid have been detected in high doses in depopulated colonies.…”
Section: Agricultural Intensification and Use Of Pesticidesmentioning
confidence: 99%
“…In the latter country, fipronil and imidacloprid have been detected in high doses in depopulated colonies. Although foliar application of fipronil was prohibited in 2009, intoxication is still a problem (Pareja et al 2011). Additionally, pesticides can also affect native bee populations in SA.…”
Section: Agricultural Intensification and Use Of Pesticidesmentioning
confidence: 99%
“…In western Uruguay, various honey bee hive matrices were collected from depopulated and healthy honey bee hives (Pareja et al 2011). Approximately 4,800 samples were obtained from eight depopulated apiaries and approximately 10,000 hive samples were obtained from 29 healthy apiaries.…”
Section: Tier-2 Characterization Of Exposurementioning
confidence: 99%
“…Bees' exposure to lethal and sublethal doses of systemic pesticides may increase motor and behavioral alterations due to continuous exposure of these pollinators to contaminated resources. The fipronil and imidacloprid detection in resources collected by bees and stored in hives (Chauzat et al, 2006;Pareja et al, 2011) confirmed the exposure of pollinators to sublethal doses of these insecticides, which can compromise the maintenance of whole colonies. Studies also have demonstrated the high toxicity of these molecules to native stingless bees (Tomé et al, 2012;Rondeau et al, 2014;Costa et al, 2015;Soares et al, 2015).…”
Section: Discussionmentioning
confidence: 76%